Treatment outcomes of high-dose chemotherapy plus stem cell rescue in high-risk neuroblastoma patients in Thailand - Kunanya Suwannaying; Piti Techavichit; Patcharee Komvilaisak; Napat Laoaroon; Nattee Narkbunnam; Kleebsabai Sanpakit; Kanhatai Chiengthong; Thirachit Chotsampancharoen; Lalita Sathitsamitphong; Chalongpon Santong; Panya Seksarn; Suradej Hongeng; et al. (The Korean Pediatric Society, 2022)
Background In 2013, the Thai Pediatric Oncology Group (ThaiPOG) introduced a national protocol in which high-dose chemotherapy plus stem cell rescue is performed without immunotherapy. Methods This study aimed to elucidate the outcomes of high-risk neuroblastoma (HR-NB) patients treated with the ThaiPOG protocol. This retrospective cohort review included 48 patients (30 males, 18 females) with a median age of 3 years (range, 8 months to 18 years) who were treated at 5 ThaiPOG treatment centers in Thailand in 2000-2018. Results Eight of the 48 patients showed MYCN amplification. Twenty-three patients (48%) received 131I-meta-iodobenzylguanidine prior to high-dose chemotherapy and stem cell rescue. The majority of patients achieved a complete or very good response prior to consolidation treatment. The 5-year overall survival (OS) and event-free survival (EFS) rates were 45.1% and 40.4%, respectively. Patients aged >2 years had a nonsignificantly higher mortality risk (hazard ratio [HR], 2.66; 95% confidence interval [CI], 0.92-7.68; P=0.07). The MYCN amplification group had lower OS and EFS rates than the MYCN nonamplification group, but the difference was not statistically significant (45% OS and 37.5% EFS vs. 33.3% OS and 16.6% EFS; P=0.67 and P=0.67, respectively). Cis-retinoic acid treatment for 12 months was a strong prognostic factor that could reduce mortality rates among HR-NB patients (HR, 0.27; 95% CI, 0.09-0.785; P=0.01). Conclusion High-dose chemotherapy plus stem cell rescue followed by cis-retinoic acid for 12 months was well tolerated and could improve the survival rates of patients with HR-NB.